The Use of the Show and Tell Method to Improve Vocabulary Mastery in The First Grade Students Of Junior High School - Enia Yasmiatun; Listyaning Sumardiyani; Maria Yosephin Widarti Lestari (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
To be effective in teaching vocabulary, teachers must identify, use, and be creative in their methods. The English teacher should employ the proper teaching technique to tackle the problem of mastering vocabulary using the Show and the Tell method. This study was purposefully intended to look into the following topics: 1) the students’ vocabulary mastery before they were taught by using Show and Tell Method 2) the students’ vocabulary mastery after they were taughtwhatwiut using Show and Tell Method 3) the significant improvement of the students’ vocabulary mastery after using Show and Tell Method. It was a quasi-experimental study that used a pretest-posttest control group research design. The sample of the research is two claClassessess research, the researchers choose tclassesass consists list VII A 27 st,udstudentsnd VII B 26 students. The test was employed as a datgatheringng instrument, and it was in the form of a test that included a pre-test and a post-test. Both the experimental and control groups were given the test. Based on the findings of data analysis using the normality, homogeneity tests, anthatteststst. It can be concluded the alternative hypothesis was accepted while the null hypothesis was rejected. It means there were significant differences in vocabulary before and afteusinged the show and tells method for the first grade Junior High School (SMP) Negeri 4 Juwana. Furthermore, tusesed of the Show and Tell Method was important teaching vocabulary mastery because could help motivate vocabularies show and tell method; vocabulary mastery; in students of junior high school.